Pengaruh Variasi Temperatur Dan Waktu Terhadap Rendemen Pirolisis Limbah Kulit Durian Menjadi Asap Cair - Nurrassyidin Nurrassyidin; Idral Idral; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Manufacturing of   Liquid Smoke from durian’s peel waste biomass  that used for preservation by pyrolysis process  to produce more valuable and reliable product. Purpose of  this research  is  to find dependence of   yield  liquid smoke from pyrolysis durian’s  peel  waste  to  temperature  and  time.  The  temperature  is  250°C,  275°C, 300°C, 325°C and 350°C also the time is 90, 120 and 150 minutes that did with one set of pyrolysis equipment. From this research has been got the result of yield at each variabel, 250°C = 5.95%, 275°C = 10.57%, 300°C = 11.12%, 325°C = 11.22% dan 350°C =19.09% and 90 minutes = 14.31%, 120 minutes = 19.10% dan 150 minutes = 26.52%. so at the highest temperature and time will be get the highest yield. Keywords: Durian’s Peel, Liquid Smoke, Preservation, Pyrolysis